CRMP4 Inhibits Bone Formation by Negatively Regulating BMP and RhoA Signaling. (2nd February 2017) - Abdallah, Basem M; Figeac, Florence; Larsen, Kenneth H; Ditzel, Nicholas; Keshari, Pankaj; Isa, Adiba; Jafari, Abbas; Andersen, Thomas L; Delaisse, Jean‐Marie; Goshima, Yoshio; Ohshima, Toshio; Kassem, Moustapha
ABSTRACT: We identified the neuroprotein collapsing response mediator protein‐4 (CRMP4) as a noncanonical osteogenic factor that regulates the differentiation of mouse bone marrow skeletal stem cells (bone marrow stromal stem cells [mBMSCs]) into osteoblastic cells. CRMP4 is the only member of the CRMP1–CRMP5 family to be expressed by mBMSCs and in osteoprogenitors of both adult mouse and human bones. In vitro gain‐of‐function and loss‐of‐function of CRMP4 in murine stromal cells revealed its inhibitory effect on osteoblast differentiation. In addition, Crmp4 ‐deficient mice ( Crmp4 –/– ) displayed a 40% increase in bone mass, increased mineral apposition rate, and bone formation rate, compared to wild‐type controls. Increased bone mass in Crmp4 –/– mice was associated with enhanced BMP2 signaling and BMP2‐induced osteoblast differentiation in Crmp4 –/– osteoblasts (OBs). Furthermore, Crmp4 –/– OBs exhibited enhanced activation of RhoA/focal adhesion kinase (FAK) signaling that led to cytoskeletal changes with increased cell spreading. In addition, Crmp4 –/– OBs exhibited increased cell proliferation that was mediated via inhibiting cyclin‐dependent kinase inhibitor 1B, p27 Kip1 and upregulating cyclin D1 expression which are targets of RhoA signaling pathway. Our findings identify CRMP4 as a novel negative regulator of osteoblast differentiation. © 2016 American Society for Bone and Mineral Research.